Influence Return on Equity Ratio, Debt to Equity Ratio, and Net Profit Margin Against Stock Price Jakarta Islamic Index - Sunggoro, Andhika Rafi (Sahabat Publikasi, 2024)
This study aims to determine the effect of ROE, DER, and NPM on Jakarta Islamic Index (JII) stock prices, either simultaneously or partially. The type of research used in this study is quantitative research using descriptive methods and verification methods using the analysis method Multiple Linear Regression, T Test, F Test, Determination Coefficient Test, and Classical Assumption Test using Stata 15 software. Based on the research results, the results the analysis explains that ROE does not have a partial effect, but DER and NPM have a partial influence on the JII Stock Price. The results of the analysis also explain that the data is not infected with multicollinearity problems and does not contain heteroscedasticity, and simultaneously ROE, DER, and NPM have no influence on the JII Share Price with the ability to explain the JII Stock Price variance of 57.58%. Then the following conclusions are obtained: 1) The results of the simultaneous analysis show no significant effect between the variables ROE, DER, and NPM on the JII Stock Price. 2) The results of the partial test, it is known that DER and NPM have a positive and significant effect, but ROE has no positive and significant effect on JII's stock price.